2008
DOI: 10.1007/s00439-008-0590-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci

Abstract: In Caucasian, several studies have identified some common variants associated with human stature variation. However, no such study was performed in Chinese, which is the largest population in the world and evidently differs from Caucasian in genetic background. To identify common or ethnic specific genes for stature in Chinese, an initial GWAS and follow-up replication study were performed. Our initial GWAS study found that a group of 13 contiguous SNPs, which span a region of ∼150 kb containing two neighborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…[12][13][14][15] GWAS on height have been reported since 2007 and our group also reported genetic variants for adult height in the Korean population and apparent ancestral differences between Koreans and Europeans. 16 Recently, 54 genetic variants were known to influence the height and all of them were results of studies conducted on adults.…”
Section: Introductionsupporting
confidence: 63%
“…[12][13][14][15] GWAS on height have been reported since 2007 and our group also reported genetic variants for adult height in the Korean population and apparent ancestral differences between Koreans and Europeans. 16 Recently, 54 genetic variants were known to influence the height and all of them were results of studies conducted on adults.…”
Section: Introductionsupporting
confidence: 63%
“…13 The authors of the Chinese study reported that 6 of the 44 SNPs identified in Caucasian individuals were also significant in a Chinese population (Po0.1, with the same direction of effect). 13 However, the number of subjects included in the Chinese GWA study was limited (n¼618), so the studies cannot be directly compared. However, we observed ethnic differences in MAFs of the SNPs present in both Caucasians and Koreans.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is unclear whether the associated loci have similar roles in Asian populations, particularly because a recent GWA study performed in a Chinese population revealed markedly different results from those obtained in a Caucasian population. 13 Recently, we performed a GWA study of eight quantitative traits (such as, human height) of biomedical importance in the Korean population. The study identified eight loci that were significantly associated with height, including HMGA1, SPAG17, ZBTB38, PLAG1, FBP2, TBX2, EFEMP1 and LTBP1.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, inconsistent results of GWA studies have been reported in East Asian populations. 10,11 For the loci showing convincing evidence of height association in Europeans, no substantial overlap was found in the GWA study involving 618 Chinese subjects, 10 whereas significant association was detected at a number of previously reported loci (that is, 14 independent loci showed Po0.05) in the GWA study involving 8842 Korean subjects. 11 Along these lines, we performed the present study to test the potential overlap of height association between East Asians and Europeans and to replicate the suggestive association signals reported by the two previous GWA studies in East Asians 10,11 using the genotype data on 1530 Japanese samples, which are part of our ongoing GWA study of cardiometabolic disorders among the Japanese (Supplementary Table 1).…”
mentioning
confidence: 79%